KARAKTERISTIK FISIKOKIMIA DAN SENSORI BERAS ANALOG MULTIGRAIN BERPROTEIN TINGGI - Ari Andika; Feri Kusnandar; Slamet Budijanto (Jurnal Teknologi dan Industri Pangan, 2021)
Several grains (green bean, red bean, soybean, corn, nuts, sesame, and millets) were processed to yield a high protein analogue rice. Red beans and green beans were soaked in water for six hours while soybean was boiled for 10 minutes and then peeled. Nuts were dried at 70°C, ground, and sieved to pass 80 mesh. All grains were ground into powder except for sesame which was in whole seed. Four formulas of rice analogues were produced at a different level of millet (0-15%), corn (35-50%) with fixed level of red beans (10%), soybeans (25%), green beans (10%), sesame (3%), and glycerol monostearate (GMS) (2%). The products were analyzed in terms of proximate composition, hardness, water absorption index, development ratio, cooking time, in vitro protein digestibility, amino acids composition, and protein digestibility-corrected amino acid score (PDCAAS). The four analogue rice formulas contained high level of protein and protein digestibility, but they did not fulfill the targeted complementation. The protein content of the analogue rice varied from 18.19 to 19.09% (wet based) with protein digestibility of 81.27-88.86%. The most preferred formulas of the rice analogue was composed of corn (40%), millet (10%, red beans (10%), soybeans (25%), green beans (10%), sesame (3%), and GMS (2%). It contained 42.48% of amino acids score and 36.53% of PDCAAS value.